Determination of Fluoxetine in Weight Loss Herbal Medicine Using an Electrochemical Sensor Based on rGO-CuNPs - Melaré, Aline Giuli [UNESP]; Barreto, Francisco Contini [UNESP]; Silva, Martin Kassio Leme [UNESP]; Simões, Rafael Plana [UNESP]; Cesarino, Ivana [UNESP] (MDPI, 2023)
The rising popularity of herbal medicine as a weight loss remedy, fueled by misleading propaganda, raises concerns about the manufacturing processes and potential inclusion of controlled substances such as fluoxetine (FLU). The objective of this work is to develop and evaluate the performance of an electrochemical device by modifying a glassy carbon electrode (GC) with a nanocomposite based on reduced graphene oxide (rGO) and copper nanoparticles (CuNPs) for detecting FLU in manipulated herbal medicines. Scanning electron microscopy (FEG-SEM) and cyclic voltammetry (CV) were applied for morphological and electrochemical characterization and analysis of the composite’s electrochemical behavior. Under optimized conditions, the proposed sensor successfully detected FLU within the range of 0.6 to 1.6 µmol L−1, showing a limit of detection (LOD) of 0.14 µmol L−1. To determine the presence of FLU in herbal samples, known amounts of the analytical standard were added to the sample, and the analyses were performed using the standard addition method, yielding recoveries between −2.13 and 2.0%.
Keywords: copper nanoparticles; electrochemical sensors; fluoxetine; herbal medicine; reduced graphene oxide